Genes Encoding Transcription Factors TaDREB5 and TaNFYC-A7 Are Differentially Expressed in Leaves of Bread Wheat in Response to Drought, Dehydration and ABA - Zotova, Lyudmila; Kurishbayev, Akhylbek; Jatayev, Satyvaldy; Khassanova, Gulmira; Zhubatkanov, Askar; Serikbay, Dauren; Sereda, Sergey; Sereda, Tatiana; Shvidchenko, Vladimir; Lopato, Sergiy; Jenkins, Colin; Soole, Kathleen; et al. (Frontiers in Plant Science, 2018)
Two groups of six spring bread wheat varieties with either high or low grain yield under the dry conditions of Central and Northern Kazakhstan were selected for analysis. Experiments were set up with the selected wheat varieties in controlled environments as follows: (1) slowly progressing drought imposed on plants in soil, (2) rapid dehydration of whole plants grown in hydroponics, (3) dehydration of detached leaves, and (4) ABA treatment of whole plants grown in hydroponics. Representatives of two different families of transcription factors (TFs), TaDREB5 and TaNFYC-A7, were found to be linked to yield-under-drought using polymorphic Amplifluor-like SNP marker assays. qRT-PCR revealed differing patterns of expression of these genes in the leaves of plants subjected to the above treatments. Under drought, TaDREB5 was significantly up-regulated in leaves of all high-yielding varieties tested and down-regulated in all low-yielding varieties, and the level of expression was independent of treatment type. In contrast, TaNFYC-A7 expression levels showed different responses in the high- and low-yield groups of wheat varieties. TaNFYC-A7 expression under dehydration (treatments 2 and 3) was higher than under drought (treatment 1) in all high-yielding varieties tested, while in all low-yielding varieties the opposite pattern was observed: the expression levels of this gene under drought were higher than under dehydration. Rapid dehydration of detached leaves and intact wheat plants grown in hydroponics produced similar changes in gene expression. ABA treatment of whole plants caused rapid stomatal closure and a rise in the transcript level of both genes during the first 30 min, which decreased 6 h after treatment. At this time-point, expression of TaNFYC-A7 was again significantly up-regulated compared to untreated controls, while TaDREB5 returned to its initial level of expression. These findings reveal significant differences in the transcriptional regulation of two drought-responsive and ABA-dependent TFs under slowly developing drought and rapid dehydration of wheat plants. The results obtained suggest that correlation between grain yield in dry conditions and TaNFYC-A7 expression levels in the examined wheat varieties is dependent on the length of drought development and/or strength of drought; while in the case of TaDREB5, no such dependence is observed.